2008
DOI: 10.3201/eid1405.070130
|View full text |Cite
|
Sign up to set email alerts
|

Bacteremia Caused by Group G Streptococci, Taiwan

Abstract: A retrospective observational study in Taiwan, 1998–2004, identified 92 patients with group G streptococcal bacteremia; 86 had Streptococcus dysgalactiae subspecies equisimilis . The most common diagnosis was cellulitis (48 cases), followed by primary bacteremia (34 cases). Infection recurred in 9 patients. Mortality rate was low (3.3%); resistance to quinupristin-dalfopristin was high.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
48
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 15 publications
(17 reference statements)
11
48
1
Order By: Relevance
“…Person-to-person transmission routes of SDSE should be determined in detail by future surveillance. The prevalence of invasive SDSE infection has increased over the years elsewhere in Asia [6,36], in Europe [37][38][39][40][41][42][43], and in America [5,31,44], as well as in Japan. As for age distribution, population-based surveillance carried out by Broyles et al (n = 212) [5] found that most patients with invasive diseases (59.0%) were adults less than 65 years old, while the majority in our study (74.0%) were at least 65 years old [3].…”
Section: Emergence Of Invasive Sdse Infectionsmentioning
confidence: 98%
See 1 more Smart Citation
“…Person-to-person transmission routes of SDSE should be determined in detail by future surveillance. The prevalence of invasive SDSE infection has increased over the years elsewhere in Asia [6,36], in Europe [37][38][39][40][41][42][43], and in America [5,31,44], as well as in Japan. As for age distribution, population-based surveillance carried out by Broyles et al (n = 212) [5] found that most patients with invasive diseases (59.0%) were adults less than 65 years old, while the majority in our study (74.0%) were at least 65 years old [3].…”
Section: Emergence Of Invasive Sdse Infectionsmentioning
confidence: 98%
“…Beginning around 2000, invasive infections such as bacteremia caused by SDSE have been reported increasingly worldwide, as well as those caused by GAS and GBS [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Some works reported recurrent bacteremia induced by SDSE [55]. There is a description of toxic shock syndrome in a neonate that took place 12 h after birth and was caused by a strain having the same emm type and PFGE pattern as the maternal one, which suggests a possibility of SDSE carrier-state in pregnant women and vertical transmission of the microorganism to a newborn, as in the case of S. agalactiae [53].…”
Section: Introductionmentioning
confidence: 99%
“…In one of the two cases the causative GAS was found to be Streptococcus equisimilis (1), commonly carrying a group C or G carbohydrate antigen, and in the other case, an intravenous drug abuser had recurrent septic arthritis and bacteremia with a GAS isolate not further classified (14). In contrast to the lack of reports of recurrent bacteremia with S. pyogenes, reports of beta-hemolytic streptococci of groups C and G, which share many features with S. pyogenes, causing recurrent bacteremia are numerous (4,10,13,16,17).The isolates from the two episodes of bacteremic infection were classified as GAS by their typical appearance by Gram staining and on blood agar, as well as by latex agglutination, according to standard laboratory procedures. T typing, as described in reference 11, identified both isolates as T28.…”
mentioning
confidence: 99%